Community-randomised controlled trial embedded in the Anishinaabek Cervical Cancer Screening Study: human papillomavirus self-sampling versus Papanicolaou cytology. Issue 10 (8th October 2016) - Zehbe, Ingeborg; Jackson, Robert; Wood, Brianne; Weaver, Bruce; Escott, Nicholas; Severini, Alberto; Krajden, Mel; Bishop, Lisa; Morrisseau, Kyla; Ogilvie, Gina; Burchell, Ann N; Little, Julian
Abstract : Objectives: The incidence of cervical cancer is up to 20-fold higher among First Nations women in Canada than the general population, probably due to lower participation in screening. Offering human papillomavirus (HPV) self-sampling in place of Papanicolaou (Pap) testing may eventually increase screening participation and reduce cervical cancer rates in this population. Design: A community-randomised controlled screening trial. Setting: First Nations communities in Northwest Ontario, Canada. Participants: Women aged between 25 and 69, living in Robinson Superior Treaty First Nations. The community was the unit of randomisation. Interventions: Women were asked to complete a questionnaire and have screening by HPV self-sampling (arm A) or Pap testing (arm B). Primary outcome measures: The number of women who participated in cervical screening. Randomisation: Community clusters were randomised to include approximately equivalent numbers of women in each arm. Results: 6 communities were randomised to arm A and 5 to arm B. One community withdrew, leaving 5 communities in each group (834 eligible women). Participation was <25%. Using clustered intention-to-treat (ITT) analysis, initial and cumulative averaged uptakes in arm A were 1.4-fold (20% vs 14.3%, p=0.628) and 1.3-fold (20.6% vs 16%, p=0.694) higher compared to arm B, respectively. Corresponding per protocol (PP) analysis indicates 2.2-fold (22.9% vs 10.6%, p=0.305) and 1.6-fold (22.9% vs 14.1%, p=0.448) higher uptakes in arm A compared to arm B. Screening uptake varied between communities (range 0–62.1%). Among women who completed a questionnaire (18.3% in arm A, 21.7% in arm B), the screening uptake was 1.8-fold (ITT; p=0.1132) or 3-fold (PP; p<0.01) higher in arm A versus arm B. Conclusions: Pap and HPV self-sampling were compared in a marginalised, Canadian population. Results indicated a preference for self-sampling. More research on how to reach underscreened Indigenous women is necessary. Trial registration number: ISRCTN84617261.